2016
DOI: 10.1002/hep.28564
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic gene transfer of human aquaporin‐1 improves bile salt secretory failure in rats with estrogen‐induced cholestasis

Abstract: The adenoviral gene transfer of human aquaporin-1 (hAQP1) water channels to the liver of 17a-ethinylestradiol-induced cholestatic rats improves bile flow, in part by enhancing canalicular hAQP1-mediated osmotic water secretion. To gain insight into the mechanisms of 17a-ethinylestradiol cholestasis improvement, we studied the biliary output of bile salts (BS) and the functional expression of the canalicular BS export pump (BSEP; ABCB11). Adenovector encoding hAQP1 (AdhAQP1) or control vector was administered b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 49 publications
5
36
0
Order By: Relevance
“…(1) In the setting of chronic liver disease (CLD), several studies have shown the presence of HEV infection in 3.2%-6.5% cases of decompensated CLD, mostly in patients with alcoholic CLD. (2) No differences were observed in terms of mortality between patients with and without HEV infection, but the number of HEV cases was low. To further investigate the impact of HEV in this setting, we conducted a prospective multicenter study on a French cohort of decompensated alcoholic CLD.…”
Section: Hepatitis E In Decompensated Alcoholic Cirrhosismentioning
confidence: 93%
See 3 more Smart Citations
“…(1) In the setting of chronic liver disease (CLD), several studies have shown the presence of HEV infection in 3.2%-6.5% cases of decompensated CLD, mostly in patients with alcoholic CLD. (2) No differences were observed in terms of mortality between patients with and without HEV infection, but the number of HEV cases was low. To further investigate the impact of HEV in this setting, we conducted a prospective multicenter study on a French cohort of decompensated alcoholic CLD.…”
Section: Hepatitis E In Decompensated Alcoholic Cirrhosismentioning
confidence: 93%
“…(1) We thank the authors for their comments in our recent studies. (2,3) Nevertheless, we believe that an analysis of the role of aquaporins (AQPs) in hepatocyte canalicular water transport and bile secretion should take into account several published contributions that were not cited in the editorial.…”
Section: To the Editormentioning
confidence: 99%
See 2 more Smart Citations
“…Though it is unlikely that AQP ‘activators’ can be identified, as the AQPs are probably already maximally active, selective transcriptional upregulators of AQP7 may reduce adipocyte hypertrophy in obesity, of AQP3 may promote wound healing, of AQP4 may have anti-epileptic activity, and of AQP5 might increase glandular fluid secretion. There is evidence that AQP gene transfer may increase epithelial water permeability, promoting saliva secretion in salivary gland disorders [2] and bile secretion in liver diseases associated with cholestasis [23]. Finally, blockers of binding of pathogenic AQP4-targeted autoantibodies to astrocyte AQP4 might prevent or reduce neuropathology and neurological deficit in neuromyelitis optica [28].…”
Section: 1 Introduction and Potential Indications Of Aquaporin Modmentioning
confidence: 99%